PENERAPAN METODE STRUKTUR ANALITIKAL SINTETIK (SAS) BERBANTUAN MEDIA KARTU HURUF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DI KELAS II SD NEGERI I TOGEME - Farmi Dermilan; Pamuti Pamuti; Suhardi Abdullah (PEDAGOGIK, 2022)
This study was conducted with the aim of knowing the process of applying the method (SAS) assisted byletter card media to improve early reading skills in grade II SD Negeri I Togeme, knowing the use of themethod (SAS) assisted by letter card media to improve early reading skills in grade II SD Negeri ITogeme. This type of research is Classroom Action Research (CAR) using qualitative and quantitativeapproaches. The PTK stages include: Planning, Implementation, Observation, Reflection which consistsof cycles I and II. The subjects in this study amounted to 16 grade II students in the even semester of the2021/2022 academic year. The data collection in this research are: Observation, Test andDocumentation. The results of the application of the method (SAS) assisted by letter card media inlearning to improve early reading skills in the first cycle showed that students' mastery was 43% of the 16students who took part in the learning process in class with an average number of 63.18% in the firstcycle. . Meanwhile, in the second cycle, 81% of the students who completed the learning process in theclassroom were 81% of the 16 students who completed the learning process with an average of 73.18%.Thus, it can be concluded that the application of the method (SAS) assisted by letter card media canimprove early reading skills in second grade students of SD Negeri I Togeme.